Development and Validation of a Life-Sized Mock Circulatory Loop of the Human Circulation for Fluid-Mechanical Studies. Issue 8 (November 2019) - Gehron, Johannes; Zirbes, Julian; Bongert, Markus; Schäfer, Stefan; Fiebich, Martin; Krombach, Gabriele; Böning, Andreas; Grieshaber, Philippe
Abstract : Mock circulatory loops (MCLs) are usually developed for assessment of ventricular assist devices and consist of abstracted anatomical structures represented by connecting tubing pipes and controllable actuators which could mimic oscillating flow processes. However, with increasing use of short-term peripheral mechanical support (extracorporeal life support [ECLS]) and the upcoming evidence of even counteracting flow processes between the failing native circulation and ECLS, MCLs incorporating the peripheral vascular system and preserved anatomical structures are becoming more important for systematic assessment of these processes. For reproducible and standardized fluid-mechanical studies using magnetic resonance imaging, Doppler ultrasound, and computational fluid dynamics measurements, we developed a MCL of the human circulation. Silicon-based life-sized dummies of the human aorta and vena cava (vascular module) were driven by paracorporeal pneumatic assist devices. The vascular module is placed in a housing with all arterial branches merging into peripheral resistance and compliances modules, and blood-mimicking fluid returns to the heart module through the venous dummy. Compliance and resistance chambers provide for an adequate simulation of the capillary system. Extracorporeal life support cannulation can be performed in the femoral and subclavian arteries and in the femoral and jugular veins. After adjusting vessel diameters using variable Hoffmann clamps, physiologic flow rates were achieved in the supraaortic branches, the renal and mesenteric arteries, and the limb arteries with physiologic blood pressure and cardiac output (4 L/min). This MCL provides a virtually physiologic platform beyond conventional abstracted MCLs for simulation of flow interactions between the human circulation and external circulation generated by ECLS. Abstract : Supplemental Digital Content is available in the text.